Foseco non-ferrous foundryman's handbook - Brown, John R. (Butterworth-Heinemann, 1999)
The Non-Ferrous Foundryman's Handbook provides a practical reference book for all those concerned with dealing with aluminium, copper and magnesium casting alloys. International SI units are used throughout, but in almost all cases conversions to the more familiar Metric and Imperial units are given. Wherever possible, Casting Alloy Specifications include equivalent specifications for several countries as well as international specifications. Individual chapters cover the casting of all types of non-ferrous metals. For each group of alloys, specifications, and typical applications are describe.